Dental caries severity in relation to selected salivary variables among a group of pregnant women in Baghdad city/Iraq - Mutlak, Nadia Q; Yas, Baydaa A (Journal of Baghdad College of Dentistry, 2017)
Background: During pregnancy many physiological, anatomical and biochemical changes take place that affect almost all body systems. In the oral pregnant women have serious changes such as more sever dental caries.This study was conducted to measure dental caries severity and selected salivary variables (salivary flow rate, PH and viscosity)and to find the relation of dental caries with these salivary variables.Subjects, materials and methods: The study group consisted of 60 pregnant women that were divided into three equal groups according to trimester (20 pregnant women in each trimester).They were selected randomly from the Maternal and Child Health Care Centers in Baghdad city, the age range was 20-25 years. In addition to 20 unmarried women as a control group and matched with age. Stimulated salivary samples were collected .Then salivary flow rate, pH and viscosity were measured. Dental caries severity was recorded by using Decay, Missing and Filled index (D1-4MFS) using the criteria described by Manjie et al, (1989). Plaque index system by Silness and LÃ¶e, (1964) was used for measuring dental plaque thickness. For measuring dental calculus the calculus index component of the periodontal diseases index (PDI) by Ramfjord (1959) was used.Results: Results of the current study revealed that dental caries parameter represented by (DMFT ,DMFS,DS and MS) were higher among pregnant than non â€“pregnant women with significant differences (p0.05).Almost all dental caries parameter were higher in the 2nd trimesters with highly significant difference (p